Diabetes: a risk factor for poor functional outcome after total knee arthroplasty. - Jasvinder A Singh; David G Lewallen (PLoS ONE, 2013)
Background To assess the association of diabetes with postoperative limitation of activities of daily living (ADLs) after primary total knee arthroplasty (TKA). Methodology/principal findings We used the prospectively collected data from the Mayo Clinic Total Joint Registry to assess the association of diabetes and diabetes with complications with moderate-severe ADL limitation 2- and 5-years after primary TKA. Multivariable logistic regression with general estimating equations adjusted for preoperative ADL limitation, comorbidity and demographic and clinical covariates. Odds ratio (OR) and 95% confidence interval (CI) are presented. 7,139 primary TKAs at 2-years and 4,234 at 5-years constituted the cohorts. In multivariable-adjusted analyses, diabetes was associated with higher odds of moderate-severe limitation at 2- and 5-years, 1.71 (95% CI: 1.26, 2.32; P = 0.001) and 1.66 (95% CI: 1.13, 2.46; P = 0.01). Respective ORs for patients with diabetes with complications were 2.73 (95% CI: 1.47, 5.07; P = 0.001) and 2.73 (95% CI: 1.21, 6.15; P = 0.016). Sensitivity analyses that adjusted for anxiety and depression or anxiety, depression and ipsilateral hip involvement showed minimal attenuation of magnitude of the association. Conclusions/significance In this large study of patients who underwent primary TKA, diabetes as well as its severity were independently associated with poorer functional outcome. Given the increasing rates of both diabetes as well as arthroplasty, more insight is needed into disease-related and treatment-related factors that underlie this higher risk of ADL limitation in patients with diabetes. Poor functional outcomes may be preventable by modifying the control of diabetes and associated comorbidity in pre- and post-arthroplasty periods.